Literary Crime in Kraigher’s Play The Shell: Analysis of Sexuality - Ocepek, Pavel (Slavia Centralis, 2024)
This paper primarily focuses on sexuality in Alojz Kraigher’s play Školjka. We start from the theory of sexuality as a social structure. We conclude that discourses about sexuality in the play derive from two strategies typical of the social organization of sexuality in modern societies. The first strategy maintains that the role of sexuality is twofold: within marriage, its primary goal is procreation, while outside it, the result is adultery. The second strategy is based on the concept of male and female sexuality, where the difference between the two concepts is most clearly manifested by the heterosexual norms of the double standard and the identifying elements of a restrictive sexual culture. The analysis proves that by the thematization of the sexuality, Kraigher joined the literary artist who, by addressing sexuality and sex in their works, play a pivotal role in shaping public discourse on sexuality and, most importantly, in reshaping sexual norms in society.